2014
DOI: 10.1111/ejn.12536
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutamate in the morphological and physiological development of dendritic spines

Abstract: Dendritic spines form the postsynaptic half of the synapse but how they form during CNS development remains uncertain, as are the factors that promote their morphological and physiological maturation. One hypothesis posits that filopodia, long motile dendritic processes that are present prior to spine formation, are the precursors to spines. Another hypothesis posits that they form directly from the dendritic shaft. We used microphotolysis of caged glutamate to stimulate individual dendritic processes in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…NMDARs interact with actin and microtubules to physically re-shape neurons in response to neuronal firing, 45,46 including formation of cytoplasmic filopodia and dendritic spines. 47,48 There are also other examples of a similar link in non-neuronal cells. In renal podocytes, NMDARs re-shape cellular foot processes that regulate glomerular filtration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…NMDARs interact with actin and microtubules to physically re-shape neurons in response to neuronal firing, 45,46 including formation of cytoplasmic filopodia and dendritic spines. 47,48 There are also other examples of a similar link in non-neuronal cells. In renal podocytes, NMDARs re-shape cellular foot processes that regulate glomerular filtration.…”
Section: Discussionmentioning
confidence: 95%
“…Our results suggest a link between NMDAR function and the cell cytoskeleton in megakaryocytes, as it is also known to occur in neurons. NMDARs interact with actin and microtubules to physically re‐shape neurons in response to neuronal firing,45, 46 including formation of cytoplasmic filopodia and dendritic spines 47, 48. There are also other examples of a similar link in non‐neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic cultures, transient excitatory synapses are formed on dendritic shafts, helping to initiate either the formation of dendritic protrusions or spines 36 , 37 . Calcium influx through NMDARs may promote dendritic growth 17 , 38 , 39 and the development of spines 37 , 40 42 . It has been shown that a lack of NMDA receptors severely affects initial spinogenesis in adult-born neurons 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that de novo spinogenesis occurs under conditions of synaptic potentiation both in vitro (Engert and Bonhoeffer ; Maletic‐Savatic et al ; Toni et al ) and in vivo (Hayashi‐Takagi et al ; Holtmaat et al ; Kopec et al ; Matsuzaki et al ; Ryan et al ; Trachtenberg et al ; Yang et al ). Glutamatergic signaling appears to be critical for this phenomenon (Fischer et al ; Kwon and Sabatini ; Mattison et al ; Richards et al ; Ultanir et al ), although other neurotransmitters such as dopamine also likely play a role (Yagishita et al ). Ultrastructural studies have shown that at least some of these newly formed spines are capable of becoming mature and stabilized to form intact synapses, albeit hours to days following de novo spine growth (Knott et al ; Nagerl et al ; Toni et al ).…”
Section: Structure and Function Of Dendritic Spinesmentioning
confidence: 99%